The impact of butyrate on glycemic control in animals and humans: a comprehensive semi-systemic review - Hamari, Nouhaila; Blaak, Ellen E.; Canfora, Emanuel E. (Frontiers in Nutrition, 2025)
The gut microbiome has been identified as a significant factor in host metabolism, playing a key role in the etiology of obesity, type 2 diabetes and cardiometabolic risk. Butyrate, produced by the gut microbiome from indigestible carbohydrates, has been shown to have beneficial effects on body weight control, inflammation, and insulin resistance, primarily evidenced by animal studies and in vitro experiments. However, translating these benefits to humans remains challenging due to variability in mode of butyrate administration or production upon fermentation of dietary fibers, as well as in butyrate absorption, and its metabolism. For instance, oral butyrate supplementation can directly increase circulating butyrate levels, thereby targeting peripheral tissues. In contrast, butyrate produced by the gut microbiome may also influence metabolism through local signaling mechanisms affecting peripheral tissues. Additionally, there may be large heterogeneity in the response of the individuals to butyrate interventions. Future research should aim to better understand butyrate kinetics and dynamics and its mechanisms in regulating intestinal and metabolic health. In human studies, longer-term, placebo-controlled trials are needed to establish the efficacy of either targeting butyrate production or supplementation in individuals with obesity and/or metabolic disturbances. Personalized dietary interventions based on individual microbiota composition and/or function and metabolic profiles may optimize butyrate production and its metabolic benefits. This could pave the way for effective butyrate-based interventions to improve metabolic health and prevent obesity-related complications.